Three-dimensional ultrasound assessment of risk factors for cystocele and Green classification in primipara - Yin, Weiwei; Ma, Qianqing; Xie, Wen; Zhu, Yuting; Wang, Junli (Frontiers in Medicine, 2022)
Background and Aims: The present study aimed to analyze the effects of factors on cystocele and the Green classification. Methods: We conducted a cross-sectional study on 357 primiparous women examined at our hospital from January 2019 to May 2021. The following data were recorded: maternal characteristics, neonatal characteristics, and factors of childbirth. It was added to the multivariate logistic regression model to determine the independent predictors of the cystocele and the Green classification. Results: A total of 242 women had cystocele, including 71 women with Green type I cystocele, 134 women with Green type II cystocele, and 37 women with Green type III cystocele. In multivariate logistic regression analysis, body mass index (BMI) at delivery was associated with cystocele, while BMI at delivery and the second stage of labor (SSL) >1 hour were independently with the distance from the symphysis pubis to the bladder neck (SPBN) abnormal (P < 0.05). BMI at examination was associated with the large retrovesical angle (RVA) (P < 0.05). BMI at delivery and the fetal right occiput anterior position (ROA) were independently associated with the distance from the symphysis pubis to the posterior wall of the bladder (SPBP) abnormal (P < 0.05), while epidural anesthesia (EDA) was the protective factor (P < 0.05). Conclusion: Primipara women should strive to avoid exposure to modifiable risk factors such as controlling weight during pregnancy, reducing weight after delivery, and shortening SSL to reduce the occurrence of cystocele.